MAJELIS TAKLIM ASY SYIFA POTRET MAJELIS TAKLIM DALAM KOMUNITAS MUSLIM MUALLAF DI BALI - Nyayu Khodijah (Pascasarjana IAIN Metro, 2019)
Asy Syifa's taklim assembly functions as an educational institution that provides basic religious teaching for its worshipers and the implementation is not much different from the learning process that takes place in schools / madrasas or in the Al-Qur'an Education Park (TPA). In the process of its implementation, this taklim assembly is strongly influenced by the socio-cultural and economic conditions of the congregation and its clerics. This can be seen from the selection of subject matter, learning process, and management. The subject matter chosen is the main material of Islamic teachings at the basic level. The learning process is dominated by teachers as a single learning resource. The management applied is a single management pattern, where the leader also serves as a secretary and treasurer of the taklim assembly.